(untitled) (Baghdad Science Journal, 2017)
134 samples of plants and animals wastes were taken from three different regions outside Baghdad and three different regions in Baghdad. 24 cellulolytic isolates fungi AO, C1, TH1, AN1, R1, TV, PG, AF, B1, L1, AP, TH, AP1, AN3, AO2, A, A1, C, F, AO1, C2, F1, CL and AP2 independent were chosen out of 48 selected fungi. The best optimal conditions for growth were 30ºC and pH 7. The isolates were identified and screened according to the colony diameter, biomass and density of spores in addition of capability to produce the hydrolytic enzymes for cellulose.